Stratospheric memory: Effects on the troposphere - Baldwin, MP; Stephenson, DB; Thompson, DWJ; Dunkerton, TJ; Charlton, AJ; O'Neill, A (American Meteorological Society, 2003)
Published We use an empirical statistical model to demonstrate significant skill in extended-range forecasts of the monthly-mean Arctic Oscillation (AO). Forecast skill derives from long-lived circulation anomalies in the lowermost stratosphere and is greatest during boreal winter. A comparison to the Southern Hemisphere provides evidence that both the timescale and predictability of the AO depend on the presence of long-lived circulation anomalies just above the tropopause. These circulation anomalies most likely affect the troposphere through changes to waves in the upper troposphere, which induce surface pressure changes corresponding to the AO. We thank T.G. Shepherd, P.H. Haynes, and D.A. Orland for discussions. The NCEP reanalysis data were obtained from the NOAA-CIRES Climate Diagnostics Center.